Form and architectural work in the projection and occurrence of architectural landscape (2021)
Architecture must consider its condition as a work of art to transcend the contingent character of the architectural object. In this respect, current investigations discuss the making and the manufacture as mediating external relations between the architecture and landscape. In opposition, the poietic befall arises through which architecture is established as a work of art. This approach was analyzed in architectural works and was demonstrated by the event in which the landscape is revealed.